Power and delay analysis of dielectric modulated dual cavity Junctionless double gate field effect transistor based label-free biosensor. (April 2022) - Jana, Gargi; Sen, Dipanjan; Debnath, Papiya; Chanda, Manash
Highlights: Detection of bio-molecules by dielectric modulated FET biosensor. Power and delay vary significantly for charged biomolecules. Dual cavity has better sensitivity than single cavity. More sensitive in sub-threshold regime. Abstract: Recently, Metal Oxide Semiconductor Field Effect Transistor (MOSFET) based biosensors have gained immense attraction as a diagnostic tool for point-of-care testing. This paper investigates the current sensitivity, power consumption, and intrinsic delay of the Dual Cavity Junction-less (JL) Double gate MOSFET-based biosensor. Dielectric modulation has been incorporated for label-free biosensing. The impact of neutral and charged biomolecules has been investigated on the current sensitivity, power consumption, and delay. Extensive simulation using SILVACO ATLAS has been done to study the effects. Efficacy of the dual cavity in comparison to the single cavity in JL-MOSFET is demonstrated in terms of better current sensitivity and less power consumption. This work demonstrates the low-power JL-MOSFET-based label-free biosensors for the implementation of cost-efficient and simpler analytical tools for the screening of drugs and biomolecules. Graphical abstract: Image, graphical abstract